STUDI PERILAKU DAN KERUSAKAN TIANG MENGGUNAKAN DATA GETARAN PILE INTEGRITY TEST - Goldyna Septania Goldyna Septania (UNIB Press, 2022)
Abstract: The foundation is one of the structures had an important function so periodic inspections are needed. This study aimed to compare the pile response towards vibration and the pile depth from the calculation results due to vibration spikes with the actual data. The apparatus used is Pile Integrity Test (PIT) based on the low strain with a 3-axis accelerometer. In this study, two conditions were tested, before and after the pile was embedded in the ground. The samples used in this study are three piles, the height is 1 meter with the first pile without damage, the second pile with one section damage, and the third pile with two section damage. The results of this study showed that the vibration spike which marked the damage was only visible on the pile before being embedded with an average deviation of 5,46%. The vibration spike showed the average pile base is at a depth of ±900 mm and is more clearly visible on the pile after being embedded. The result found that this apparatus can detect the base of the pile with an average deviation of 6,98%.